2018
DOI: 10.25133/jpssv26n2.011
|View full text |Cite
|
Sign up to set email alerts
|

The Decision to Retire Early: Evidence from Private Service Sector in Thailand

Abstract: Using worker survey data from the Foundation of Thai Gerontology Research and Development Institute, this

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(30 reference statements)
0
0
0
Order By: Relevance
“…Gender and education have also been found by researchers to be underlying factors responsible for early retirement. Tangtipongkul & Srisuchart (2018) found that males have a significant tendency to delay their retirement compared to females by approximately 6.04%, while workers with a low level of education have a tendency to delay their retirement time by approximately 12.07% compared to well educated workers. With regards to gender, according to the quantitative study of Syam & Bakroh (2020), titled "Factors affecting early retirement decision in crises" carried out in the middle of the COVID-19 pandemic in Indonesia, results proofed that women have the probability to retire earlier than men.…”
Section: Empirical Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Gender and education have also been found by researchers to be underlying factors responsible for early retirement. Tangtipongkul & Srisuchart (2018) found that males have a significant tendency to delay their retirement compared to females by approximately 6.04%, while workers with a low level of education have a tendency to delay their retirement time by approximately 12.07% compared to well educated workers. With regards to gender, according to the quantitative study of Syam & Bakroh (2020), titled "Factors affecting early retirement decision in crises" carried out in the middle of the COVID-19 pandemic in Indonesia, results proofed that women have the probability to retire earlier than men.…”
Section: Empirical Literature Reviewmentioning
confidence: 97%
“…In addition to health and education, geographical factors also play a role in early retirement decisions. According to Tangtipongkul & Srisuchart (2018), in their study titled, "The Decision to Retire Early: Evidence from Private Service Sector in Thailand", with the assumption that, geographic region, industry, gender, age, education, and attitude towards the workplace have an influence on early retirement. Tangtipongkul & Srisuchart (2018) used statistical and regression model and found that workers in the northeastern and northern regions have a high tendency to retire early (approx.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%